Questions about the relationship between domestic violence and membership of a 1% motorcycle club - Janssen, Janine (Outlaw bikers as organized crime, 2025)
Not much attention has been paid toward the relationship between domestic violence and membership of a 1% motorcycle club. Professionals working in shelters with victims of domestic violence have regular encounters with the – often – female (ex-)partners of 1% motorcycle club members. This chapter examines what is known about the domestic situation of these victims before they came to a shelter. Does membership of a motorcycle club of (former) spouses influence the work of professionals in shelters? Based on thirteen semi-structured interviews with eleven professionals and two victims, it was difficult to establish a direct link between domestic violence and membership of a 1% motorcycle club. Therefore, further research on the following three important topics is recommended: comparisons between the family life of bikers of 1% clubs compared to other groups associated and involved with organized crime; comparisons between the experiences of domestic violence of (former) spouses of members of 1% clubs and other cases of domestic violence; and, finally, paying attention toward the handling of these cases by different professionals.